Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Karns, Rebecca; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
If iron supplementation is absent in newborn piglets, anemia will most likely occur due to iron deficiency. Typically, 200 mg of iron supplementation must be administered within 3 days of birth. In this experiment, various dosages of Gleptoforte were administered to newborn piglets to determine the most effective dosage based off of sow and litter performance. In total, 336 newborn piglets from 28 litters were evenly distributed from each sow and used in a farrowing study to establish the effects of Gleptoforte. The study took place over the course of 21 days. On day 3, all piglets were weighed and six gilts and six barrows per litter were assigned to a treatment based on a completely randomized design. Therefore, a total of 56 piglets were used for each treatment. The treatments administered entailed a negative control, 50, 100, 150, 200, or 200 mg plus a 100 mg booster on day 11 of farrowing. One mL of Gleptoforte equates to 200 mg of iron. The weigh days took place on day 3, day 11, and day 21 to compute ADG throughout the course of the experiment. On day 3, 11, and 21, one barrow per treatment per litter was used to collect a blood sample in order to observe blood criteria. Hemoglobin, Hematocrit, Serum Fe, and Total Iron Binding Capacity were measured. The feed consumed by sows during lactation was comprised of 110 mg/kg added iron from ferrous sulfate. Unsurprisingly, the negative control treatment pigs grew less than the other treatments. ADG and day 21 BW improved when the dosage of Gleptoforte administered increased (quadratic; P=.001). The treatment of 200 mg + 100 mg of Gleptoforte revealed an enhancement of hematological criteria, although it did not affect piglet growth performance compared to the 200 mg treatment. Based off of growth performance, 100 mg of Gleptoforte was determined to have the greatest effect on suckling piglets. Considering the appropriate dosage of Gleptoforte was found to be 100 mg, Gleptoforte may be the most cost effective iron supplementation when compared to other iron supplementations.
Keywords: Fall 2017